Sosialisasi dan Pelatihan Pemanfaatan Limbah Kerabang Telur sebagai Pupuk Organik Ramah Lingkungan bersama Kader PKK di Desa Karangampel - Tania Avianda Gusman Tania; Arif Nurudin; Badawi; Ali Jufri; Zakiyyah (Altifani Journal: International Journal of Community Engagement, 2025)
Eggshell waste in Karangampel Village, Indramayu, has not been optimally utilized and has the potential to cause environmental problems. In fact, eggshells are rich in calcium carbonate (CaCO₃), which is very useful as organic fertilizer. This community service activity aims to increase the knowledge and skills of PKK cadres in processing eggshell waste into environmentally friendly and useful organic fertilizer. The activity was carried out in three stages: (1) Preparation and identification of initial needs; (2) Socialization and practical training on how to make fertilizer; and (3) Qualitative evaluation through structured group discussions. This activity was attended by 20 PKK members from Karangampel Village. The results of the activity showed an increase in understanding and enthusiasm among the participants. Participants not only understood the theory but also successfully practiced fertilizer production and began applying it to vegetable plants at home. Soil pH test results also showed an increase from 7.4 to 7.5 after applying the fertilizer, indicating an improvement in soil quality. This activity successfully transformed waste into a useful product, reduced environmental pollution, and opened up creative economic potential for the community through organic fertilizer products.